SOME BEE PRODUCTS AS ANTIPARASITIC REMEDIES - D. S. Salkova (Российский паразитологический журнал, 2016)
Honeybee gives people one of the most valuable and healthy foods. These are honey, propolis, royal jelly, bee pollen, bee venom, wax. The healing properties of bee products are described in manuscripts discovered in ancient Egypt, Greece and China. Many of them are widely used in medicine for the treatment of bacterial and viral infections, to enhance the immunity of organism, for treatment of poorly healing wounds, in a variety of tumor diseases, in the gastro-intestinal diseases, promote the potency and fertility. Bee products have comparable healing properties to established drugs but they have fewer side effects. In this work we present some of the experiments that explore the impact of bee products to different parasites.